Aliphatic polycarbonate resin, crosslinked aliphatic polycarbonate resin and method for producing same, and adhesive sheet

By using the new aliphatic polycarbonate resin prepared by carbon dioxide, the problems of insufficient rigidity and adhesion of existing polycarbonate resins are solved, and low glass transition temperature and good adhesion are achieved, which are suitable for adhesion applications of various materials.

CN119907822APending Publication Date: 2025-04-29LINTEC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380066953.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-19
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Due to the rigidity of the polycarbonate structure and high glass transition temperature (Tg), the existing polycarbonate resins are difficult to adapt to the fields of softness requirements, and the adhesion to low-polar materials is insufficient, and it is difficult to achieve both high-polar and low-polar materials.

Method used

Using carbon dioxide as the preparation raw material, a new aliphatic polycarbonate resin was developed, which has an ether structure on the main chain and forms a structure through random copolymerization. The side chains contain crosslinkable functional groups, which reduces the glass transition temperature (Tg) and improves adhesion.

Benefits of technology

Low glass transition temperature (Tg) is achieved, suitable for areas of softness requirements, while exerting good adhesion to both high and low polar materials and improving retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907822A_ABST
    Figure CN119907822A_ABST
Patent Text Reader

Abstract

Provided is an aliphatic polycarbonate resin having an ether structure in the main chain thereof, and having a structure obtained by randomly copolymerizing a repeating unit represented by formula (Ia), a repeating unit represented by formula (Ib), a repeating unit represented by formula (Ic), and a repeating unit represented by formula (Id). As a result, it is possible to provide: a novel aliphatic polycarbonate resin having a low glass transition temperature (Tg) and using carbon dioxide as a raw material for production; and an aliphatic polycarbonate resin crosslinked product. In formula (Ia) and formula (Ib) # imgabs0 #, R1 and R2 each represents a hydrocarbon group having 4 or more carbon atoms, and may be the same as or different from each other. In formula (Ic) and formula (Id), R3 and R4 represent a hydrocarbon group having a crosslinkable functional group, and may be the same as or different from each other.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel aliphatic polycarbonate resin, a cross-linked aliphatic polycarbonate resin, a method for preparing the cross-linked aliphatic polycarbonate resin, and an adhesive sheet using the aliphatic polycarbonate resin in an adhesive. Background Art

[0002] In recent years, as the call for building a recycling-oriented society has increased, gases such as carbon dioxide, methane, and carbon monoxide have attracted attention as sustainable carbon raw materials. For example, it has been reported that aliphatic polycarbonates with only aliphatic (non-aromatic) groups in the main chain can be prepared by copolymerizing carbon dioxide and epoxides, and chemical products using gases such as carbon dioxide as raw materials and their preparation technology have attracted attention.

[0003] Since carbon dioxide is pointed out as a factor that causes global warming, the effective utilization of carbon dioxide discharged from factories during the process of manufacturing various materials can help protect the environment.

[0004] Patent Document 1 proposes a polyalkylene carbonate resin containing three types of repeating units, which is obtained by copolymerizing an epoxide compound, a compound having an epoxy group and an acrylate structure, and carbon dioxide in the presence of a heterogeneous catalyst.

[0005] On the other hand, acrylic adhesives containing acrylic polymers as the main component have been widely used as adhesives. Acrylic polymers are generally obtained by polymerizing monomers mainly containing (meth)acrylic acid alkyl esters having an alkyl group with 2 to 12 carbon atoms.

[0006] Although the acrylic adhesive exhibits good adhesion to materials with high polarity surfaces (high polarity materials) such as glass, polycarbonate resin, and acrylic resin, it is difficult to exhibit good adhesion to materials with low polarity surfaces (low polarity materials) such as polyolefin resins such as polyethylene and polypropylene.

[0007] Therefore, tackifier resins are added to acrylic adhesives to improve the adhesion to low-polar materials. However, if the adhesion to low-polar materials is increased, the adhesion to high-polar materials will tend to decrease, and it is not easy to balance the adhesion to both materials. In addition, as a characteristic of adhesives, in addition to adhesion, retention is also an important factor.

[0008] In this regard, Patent Document 2 proposes a photopolymerizable composition that is photopolymerized by ultraviolet light, which contains a monomer mainly composed of a (meth)acrylic acid alkyl ester having an alkyl group with 2 to 12 carbon atoms, a tackifier resin and a photopolymerization initiator, and the tackifier resin is composed of a hydrogenated alicyclic hydrocarbon resin having a specified amount of hydroxyl groups and a hydrogenated alicyclic hydrocarbon resin.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application No. 2015-533920

[0012] Patent Document 2: Japanese Patent Application Publication No. 2003-96116 Summary of the invention

[0013] 1. Technical issues to be resolved

[0014] The technical problem of the invention described in Patent Document 1 is to provide a polyalkylene carbonate resin that can exhibit thermal stability, a larger molecular weight, and improved mechanical properties such as strength. Conventional polycarbonate resins, including this polyalkylene carbonate resin, have a high glass transition temperature (Tg) due to the rigidity of their polycarbonate structures. Therefore, they are not suitable for fields requiring flexibility and adhesives.

[0015] The present invention is implemented in view of the above actual situation, and its purpose is to provide a novel aliphatic polycarbonate resin and aliphatic polycarbonate resin crosslinked product with low glass transition temperature (Tg) using carbon dioxide as a preparation raw material, and a method for preparing a novel aliphatic polycarbonate resin crosslinked product with low glass transition temperature (Tg) using carbon dioxide as a preparation raw material. In addition, the present invention also aims to provide an adhesive sheet that uses carbon dioxide as a preparation raw material, has good adhesion to both high-polarity materials and low-polarity materials, and has excellent retention.

[0016] (II) Technical solution

[0017] In order to achieve the above-mentioned purpose, first, the present invention provides an aliphatic polycarbonate resin having an ether structure on the main chain and having a structure formed by random copolymerization of a repeating unit represented by the following formula (Ia), a repeating unit represented by the following formula (Ib), a repeating unit represented by the following formula (Ic) and a repeating unit represented by the following formula (Id) (Invention 1).

[0018] [Chemical formula 1]

[0019]

[0020] In formula (Ia) and formula (Ib), R 1 and R 2 are hydrocarbon groups having 4 or more carbon atoms, and may be the same or different from each other. In formula (Ic) and formula (Id), R 3 and R 4 are hydrocarbon groups having a crosslinkable functional group, and may be the same as or different from each other.

[0021] In the aliphatic polycarbonate resin of the above invention (Invention 1), the above R 1 and R 2 The hydrocarbon group has more than 4 carbon atoms and the hydrocarbon group of the side chain is relatively long, so the glass transition temperature (Tg) becomes low, which is suitable for fields requiring flexibility. In addition, since the hydrocarbon group of the side chain is relatively long, it exhibits viscosity and is particularly suitable as an adhesive. 3 and R 4 The hydrocarbon group has a crosslinkable functional group, and can exert good cohesive force by crosslinking (preferably self-crosslinking) through the crosslinkable functional group, thereby becoming a more excellent adhesive. In addition, the aliphatic polycarbonate resin can be prepared using carbon dioxide as a raw material, thereby achieving effective utilization of carbon dioxide.

[0022] In the above invention (Invention 1), it is preferred that the crosslinkable functional group is a (meth)acryloyl group or an allyl group (Invention 2).

[0023] In the above inventions (Inventions 1 and 2), it is preferred that: 3 or the R 4 Having an alkyl chain (Invention 3).

[0024] In the above inventions (Inventions 1 to 3), it is preferred that: 3 or the R 4 It has an ether structure (Invention 4).

[0025] In the above inventions (Inventions 1 to 4), it is preferred that: 3 or the R 4 It includes a structure represented by the following formula (II) (Invention 5).

[0026] CH2=CH-C(=O)-OXO- ···(II)

[0027] In formula (II), X is an alkyl chain.

[0028] In the above inventions (Inventions 1 to 5), it is preferred that the aliphatic polycarbonate resin contains 0.01 mol % or more and 10 mol % or less of the crosslinkable functional group (Invention 6).

[0029] In the above inventions (Inventions 1 to 6), it is preferred that the aliphatic polycarbonate resin contains 0.1% by mass or more and 99% by mass or less of the unit of the ether structure on the main chain (Invention 7).

[0030] In the above inventions (Inventions 1 to 7), it is preferred that the aliphatic polycarbonate resin is a polymerization reaction product of carbon dioxide and epoxide (Invention 8).

[0031] In the above inventions (Inventions 1 to 8), it is preferred that the glass transition temperature (Tg) of the aliphatic polycarbonate resin is 5° C. or less (Invention 9).

[0032] Second, the present invention provides an aliphatic polycarbonate resin cross-linked product obtained by cross-linking the aliphatic polycarbonate resins (Inventions 1 to 9) (Invention 10).

[0033] In the above invention (Invention 10), it is preferred that the gel fraction of the aliphatic polycarbonate resin cross-linked product is 15% or more and 85% or less (Invention 11).

[0034] In the above inventions (Inventions 10 and 11), it is preferred that the 5% weight loss temperature of the aliphatic polycarbonate resin crosslinked product is 200° C. or higher and 450° C. or lower (Invention 12).

[0035] Thirdly, the present invention provides a method for preparing a crosslinked aliphatic polycarbonate resin, wherein the aliphatic polycarbonate resin (Inventions 1 to 9) is irradiated with energy rays to crosslink the aliphatic polycarbonate resin (Invention 13).

[0036] Fourthly, the present invention provides an adhesive sheet comprising an adhesive layer composed of an adhesive, wherein the adhesive contains 50% by mass or more of an aliphatic polycarbonate resin having an ether structure on the main chain and a crosslinkable functional group on the side chain, wherein the adhesive sheet has an adhesive force to polypropylene of 1.5 N / 25 mm or more (Invention 14).

[0037] The adhesive sheet of the above invention (Invention 14) has the above-mentioned structure and physical properties, and thus exhibits good adhesive force to both high-polarity materials and low-polarity materials, and also has excellent holding power.

[0038] Fifth, the present invention provides an adhesive sheet comprising an adhesive layer composed of an adhesive, wherein the adhesive contains 50% by mass or more of an aliphatic polycarbonate resin crosslinked product, wherein the aliphatic polycarbonate resin crosslinked product is a crosslinked product of an aliphatic polycarbonate resin having an ether structure on the main chain and a crosslinkable functional group on the side chain, and the adhesive strength of the adhesive sheet to polypropylene is 1.5 N / 25 mm or more (Invention 15).

[0039] The adhesive sheet of the invention (Invention 15) has the above-mentioned structure and physical properties, and has good adhesion to both high-polarity materials and low-polarity materials, and also has excellent retention. In particular, the aliphatic polycarbonate resin crosslinked product is formed by crosslinking the aliphatic polycarbonate resin, and has good cohesive force, and has even better adhesion and retention.

[0040] In the above invention (Invention 15), it is preferred that: as the holding force based on JIS Z0237: 2009, the adherend is set to stainless steel, the attachment area is set to 25 mm×25 mm, the temperature during the test is set to 40°C, and when a load of 9.8 N is applied, the time until the adhesive sheet falls off is more than 8000 seconds (Invention 16).

[0041] In the above invention (Invention 14), it is preferred that the aliphatic polycarbonate resin is the aliphatic polycarbonate resin (Inventions 1 to 9) (Invention 17).

[0042] In the above invention (Invention 15), it is preferred that the aliphatic polycarbonate resin cross-linked product is the aliphatic polycarbonate resin cross-linked product (Invention 10) (Invention 18).

[0043] (III) Beneficial effects

[0044] According to the present invention, a novel aliphatic polycarbonate resin and aliphatic polycarbonate resin crosslinked product with carbon dioxide as a raw material and a low glass transition temperature (Tg) can be provided. In addition, according to the preparation method of the present invention, a novel aliphatic polycarbonate resin crosslinked product with carbon dioxide as a raw material and a low glass transition temperature (Tg) can be prepared. In addition, the adhesive sheet of the present invention uses carbon dioxide as a raw material for preparation, and has good adhesion to both high-polarity materials and low-polarity materials, and excellent retention. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a cross-sectional view of an adhesive sheet according to one embodiment of the present invention.

[0046] Figure 2 This is a cross-sectional view of an adhesive sheet according to another embodiment of the present invention.

[0047] Figure 3 To show the polymer prepared in Example 1 1 This is a graph showing the measurement results of H-NMR.

[0048] Figure 4 To show the polymer prepared in Comparative Example 1 1 This is a graph showing the measurement results of H-NMR. DETAILED DESCRIPTION

[0049] Hereinafter, embodiments of the present invention will be described.

[0050] [Aliphatic polycarbonate resin]

[0051] An aliphatic polycarbonate resin according to one embodiment of the present invention (hereinafter sometimes referred to as "aliphatic polycarbonate resin A") has an ether structure on the main chain and has a structure formed by random copolymerization of a repeating unit represented by the following formula (Ia), a repeating unit represented by the following formula (Ib), a repeating unit represented by the following formula (Ic) and a repeating unit represented by the following formula (Id) (hereinafter sometimes referred to as "structure SA").

[0052] [Chemical formula 1]

[0053]

[0054] In formula (Ia) and formula (Ib), R 1 and R 2 are hydrocarbon groups having 4 or more carbon atoms, and may be the same or different from each other. In formula (Ic) and formula (Id), R 3 and R 4 are hydrocarbon groups having a crosslinkable functional group, and may be the same as or different from each other.

[0055] Since R in the above structure SA 1 and R 2 The aliphatic polycarbonate resin A is a hydrocarbon group having 4 or more carbon atoms, and the hydrocarbon group of the side chain is relatively long, so the glass transition temperature (Tg) of the aliphatic polycarbonate resin A becomes lower. Therefore, it is suitable for fields requiring flexibility, for example, it can be used in adhesives, adhesives, coating agents, etc. In addition, the aliphatic polycarbonate resin A exhibits viscosity due to the relatively long hydrocarbon group of the side chain, and is therefore suitable as an adhesive. Furthermore, since R in the above structure SA 3 and R 4 The aliphatic polycarbonate resin A is a hydrocarbon group having a crosslinkable functional group. By crosslinking (preferably self-crosslinking) via the crosslinkable functional group, the aliphatic polycarbonate resin A can exert good cohesive force and become a more excellent adhesive.

[0056] In addition, as described below, the aliphatic polycarbonate resin A can be prepared using carbon dioxide as a raw material. Therefore, the aliphatic polycarbonate resin A can achieve effective use of carbon dioxide during preparation.

[0057] As described above, R in formula (Ia) and formula (Ib) 1 and R 2The hydrocarbon group is a hydrocarbon group having 4 or more carbon atoms. Examples of the hydrocarbon group include alkyl groups and aryl groups such as phenyl groups, among which alkyl groups are preferred. As the alkyl group, an alkyl group having 4 to 20 carbon atoms is preferred, an alkyl group having 5 to 18 carbon atoms is more preferred, an alkyl group having 6 to 10 carbon atoms is particularly preferred, and an alkyl group having 6 to 9 carbon atoms is further preferred.

[0058] The above-mentioned alkyl group can be straight-chain or branched, and can also have a cyclic structure, but is preferably straight-chain or branched. As a preferred straight-chain alkyl group, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc. can be listed, and as a preferred branched alkyl group, 2-ethylhexyl, 2-methylpentyl, etc. can be listed. Among them, from the perspective of low glass transition temperature (Tg) and showing viscosity, n-octyl, n-decyl or n-dodecyl are preferred, and n-octyl or n-decyl are particularly preferred, and n-octyl is further preferred. In addition, the above-mentioned alkyl group may have a substituent.

[0059] The aliphatic polycarbonate resin A may contain two or more R 1 , and may contain more than two types of R 2 In addition, as mentioned above, R 1 and R 2 They may be the same as or different from each other.

[0060] As described above, R in formula (Ic) and formula (Id) 3 and R 4 It is a hydrocarbon group having a crosslinking functional group. Examples of the crosslinking functional group include (meth)acryloyl; alkenyl groups such as allyl and vinyl; alkynyl; alkoxy, oxy(meth)acryloyl, etc. Among them, from the perspective of self-crosslinking, (meth)acryloyl or allyl is preferred, and (meth)acryloyl is particularly preferred. In addition, in this specification, (meth)acryloyl refers to acryloyl and methacryloyl. The same applies to other similar terms.

[0061] The above R 3 or R 4 It is preferred to have an alkyl chain, and particularly preferably a linear alkyl chain. Thus, flexibility can be ensured even after cross-linking, making it a more excellent adhesive. From the perspective of this effect, the number of carbon atoms in the alkyl chain is preferably 1 to 20, more preferably 2 to 15, particularly preferably 3 to 10, and further preferably 4 to 8. In addition, the alkyl chain may have a substituent.

[0062] The above R 3 or R 4 It is preferable to have an ether structure. Thus, flexibility can be imparted to the obtained aliphatic polycarbonate resin A.

[0063] The above R3 or R 4 Specifically, it is preferable to include a structure represented by the following formula (II) or formula (III). This allows the reaction of the crosslinkable functional group to proceed efficiently regardless of the length of the alkyl chain of the side chain.

[0064] CH2=CH-C(=O)-OXO- ···(II)

[0065] In formula (II), X is an alkyl chain.

[0066] CH2=CH-CH2-YO- ···(III)

[0067] In formula (III), Y is a single bond or an alkyl chain.

[0068] In addition, the above R 3 or R 4 Specifically, a structure represented by the following formula (IV) or formula (V) is particularly preferred.

[0069] CH2=CH-C(=O)-OXO-CH2- ···(IV)

[0070] In formula (IV), X is an alkyl chain.

[0071] CH2=CH-CH2-YO-CH2- ···(V)

[0072] In formula (V), Y is a single bond or an alkyl chain.

[0073] The number of carbon atoms in the alkyl chain (X) in the above formula (II) and formula (IV) is preferably 1 to 10, more preferably 2 to 8, particularly preferably 3 to 6, and further preferably 4 to 5. In addition, the number of carbon atoms in the alkyl chain (Y) in the above formula (III) and formula (V) is preferably 1 to 10, more preferably 1 to 8, particularly preferably 2 to 6, and further preferably 2 to 4.

[0074] The aliphatic polycarbonate resin A may contain two or more R 3 , and may contain more than two types of R 4 In addition, as mentioned above, R 3 and R 4 They may be the same as or different from each other.

[0075] The aliphatic polycarbonate resin A preferably contains 0.01 mol % or more, more preferably 0.05 mol % or more, particularly preferably 0.1 mol % or more, and further preferably 0.3 mol % or more of the crosslinkable functional group (R 3 and R 4In addition, the aliphatic polycarbonate resin A preferably contains 10 mol% or less, more preferably 5 mol% or less, particularly preferably 3 mol% or less, and further preferably 1 mol% or less of the crosslinkable functional group. The aliphatic polycarbonate resin A can form a good crosslinked structure by containing the crosslinkable functional group in the above amount, and exerts excellent cohesive force as an adhesive.

[0076] The aliphatic polycarbonate resin A preferably contains 0.1 mol% or more, more preferably 0.5 mol% or more, particularly preferably 0.8 mol% or more, and further preferably 1 mol% or more of the units of the ether structure on the main chain (the repeating units represented by the formula (Ib) and the repeating units represented by the formula (Id)). In addition, the aliphatic polycarbonate resin A preferably contains 99 mol% or less, more preferably 50 mol% or less, particularly preferably 20 mol% or less, and further preferably 10 mol% or less of the units of the ether structure. By containing the units of the ether structure in the above amount, the aliphatic polycarbonate resin A effectively lowers the glass transition temperature (Tg) and can better exert the viscosity. In addition, if the content ratio of the ether structure unit in the aliphatic polycarbonate resin A is increased, the glass transition temperature (Tg) of the aliphatic polycarbonate resin A is further reduced, and the viscosity of the adhesive tends to increase.

[0077] The number average molecular weight of the aliphatic polycarbonate resin A is preferably 15,000 or more, more preferably 20,000 or more, particularly preferably 50,000 or more, and further preferably 80,000 or more. In addition, the number average molecular weight of the aliphatic polycarbonate resin A is preferably 2 million or less, more preferably 1 million or less, particularly preferably 500,000 or less, and further preferably 300,000 or less. By making the number average molecular weight of the aliphatic polycarbonate resin A within the above range, the viscosity becomes better, and the cohesive force after cross-linking also becomes good. In addition, the number average molecular weight in this specification is a value converted to standard polystyrene measured by gel permeation chromatography (GPC).

[0078] The glass transition temperature (Tg) of the aliphatic polycarbonate resin A is preferably 5°C or less, more preferably -10°C or less, particularly preferably -20°C or less, and further preferably -25°C or less. As a result, the flexibility is excellent and the viscosity is further improved. The aliphatic polycarbonate resin A can achieve the above-mentioned low glass transition temperature (Tg) by having the above-mentioned structure.

[0079] In addition, the glass transition temperature (Tg) of the aliphatic polycarbonate resin A is preferably -60°C or higher, more preferably -55°C or higher, particularly preferably -45°C or higher, and further preferably -40°C or higher. As a result, the cohesive force after crosslinking becomes good. In addition, the method for measuring the glass transition temperature (Tg) in this specification is shown in the test examples described below.

[0080] The gel fraction of the aliphatic polycarbonate resin A is preferably 1 to 30%, particularly preferably 2 to 20%, and further preferably 4 to 10%. Thus, the gel fraction after crosslinking easily falls within the preferred range described below. In addition, the method for measuring the gel fraction in this specification is shown in the test examples described below.

[0081] The 5% weight loss temperature of the aliphatic polycarbonate resin A is preferably 210 to 450° C., particularly preferably 220 to 400° C., and further preferably 230 to 350° C. As a result, the 5% weight loss temperature after crosslinking is easily within the preferred range described below. In addition, the method for measuring the 5% weight loss temperature in this specification is as shown in the test examples described below.

[0082] The aliphatic polycarbonate resin A is preferably a polymerization product of carbon dioxide and an epoxide. The aliphatic polycarbonate resin A can be preferably prepared by a preparation method comprising the following steps: in the presence of a polymerization catalyst, if necessary, controlling the water content to a predetermined amount or less, carbon dioxide (CO2), and R in the above formula (Ia) and formula (Ib) are reacted to form a polymerization product. 1 , R 2 Epoxides (hereinafter sometimes referred to as "epoxide E1") and R in the above formula (Ic) and formula (Id) 3 , R 4 The process of polymerizing an epoxide (hereinafter sometimes referred to as "epoxide E2") of the aliphatic polycarbonate resin A (for example, refer to "International Publication No. 2011 / 142259"). By selecting an appropriate polymerization catalyst, an ether structure can be introduced into the main chain of the aliphatic polycarbonate resin A. Since the aliphatic polycarbonate resin A can use carbon dioxide as a raw material for preparation, carbon dioxide can be effectively utilized.

[0083] The above-mentioned epoxide E1 is not particularly limited as long as it is an epoxide that can form a repeating unit represented by the formula (Ia) and a repeating unit represented by the formula (Ib) in the above-mentioned structure SA through the above-mentioned polymerization reaction, but is preferably a compound represented by the following formula (VI) or a derivative of the compound. In addition, in this specification, "derivative" refers to a compound formed by replacing one or more hydrogen atoms of the original compound with a group (substituent) other than a hydrogen atom.

[0084] [Chemical formula 3]

[0085]

[0086] In formula (VI), p is an integer of 3 or more.

[0087] In the formula (VI), p is preferably 3-15, more preferably 4-13, particularly preferably 5-11, and even more preferably 6-9.

[0088] As the above-mentioned epoxide E1, specifically, 1,2-butylene oxide, 1,2-pentylene oxide, 1,2-hexylene oxide, 1,2-heptylene oxide, 1,2-octylene oxide, 1,2-nonylene oxide, 1,2-decylene oxide, 1,2-undecylene oxide, 1,2-dodecylene oxide, etc. can be listed. Among them, from the perspective of low glass transition temperature (Tg) and viscosity, 1,2-hexylene oxide, 1,2-octylene oxide, 1,2-decylene oxide, etc. are preferred, 1,2-octylene oxide or 1,2-decylene oxide is particularly preferred, and 1,2-decylene oxide is further preferred. In addition, the above-mentioned epoxides may have a substituent.

[0089] The above-mentioned epoxide E2 is not particularly limited as long as it is an epoxide that can constitute a repeating unit represented by formula (Ic) and a repeating unit represented by formula (Id) in the above-mentioned structure SA through the above-mentioned polymerization reaction, but is preferably a compound represented by the following formula (VII) or formula (VIII) or a derivative of the compound.

[0090] [Chemical formula 4]

[0091]

[0092] [Chemical formula 5]

[0093]

[0094] CL in formula (VII) and formula (VIII) is a crosslinkable functional group. As a crosslinkable functional group, R in the above formula (Ic) and formula (Id) 3 and R 4 The crosslinkable functional groups they have are the same. Among them, CL in formula (VII) is preferably a (meth)acryloyl group, and CL in formula (VIII) is preferably an allyl group.

[0095] X in formula (VII) is an alkyl chain. The number of carbon atoms in the alkyl chain is the same as the number of carbon atoms in the alkyl chain (X) in the aforementioned formula (II) and formula (IV). In addition, Y in formula (VIII) is a single bond or an alkyl chain. The number of carbon atoms in the alkyl chain is the same as the number of carbon atoms in the alkyl chain (Y) in the aforementioned formula (III) and formula (V).

[0096] As the above-mentioned epoxide E2, specifically, 4-hydroxymethyl (meth) acrylate glycidyl ether, 4-hydroxyethyl (meth) acrylate glycidyl ether, 4-hydroxypropyl (meth) acrylate glycidyl ether, 4-hydroxybutyl (meth) acrylate glycidyl ether, 4-hydroxypentyl (meth) acrylate glycidyl ether, 4-hydroxyhexyl (meth) acrylate glycidyl ether and the like 4-hydroxyalkyl (meth) acrylate glycidyl ether; allyl glycidyl ether; allyl alkyl glycidyl ethers such as allyl methyl glycidyl ether, etc. can be listed. Among them, from the perspective of flexibility after cross-linking and suitability as an adhesive, 4-hydroxybutyl (meth) acrylate glycidyl ether or allyl glycidyl ether is preferred, and 4-hydroxybutyl acrylate glycidyl ether is particularly preferred. In addition, the above-mentioned epoxides may have a substituent.

[0097] The epoxide E1 and the epoxide E2 used in the step of performing the polymerization reaction may be used alone or in combination of two or more. When two or more epoxides are used, the combination and ratio thereof may be appropriately adjusted depending on the purpose.

[0098] The molar ratio of the epoxide E1 to the epoxide E2 used in the polymerization reaction step is preferably 99.99:0.01 to 90:10, more preferably 99.95:0.05 to 95:5, particularly preferably 99.9:0.1 to 99:1, and even more preferably 99.7:0.3 to 99.5:0.5.

[0099] The polymerization catalyst used in the preparation of the aliphatic polycarbonate resin A is not particularly limited as long as it is a polymerization catalyst that can introduce an ether structure into the main chain of the aliphatic polycarbonate resin A, but a double metal cyanide complex catalyst (DMC catalyst) is preferred. As the metal in the DMC catalyst, a combination of cobalt and zinc, a combination of cobalt and nickel, a combination of zinc and nickel, etc. are preferred, among which a combination of cobalt and zinc is particularly preferred. As the DMC catalyst, Zn3(Co[CN]6)2, Co(Ni[CN]4), Zn(Ni(CN)4), etc. are preferred, among which Zn3(Co[CN]6)2 is particularly preferred.

[0100] As described above, the polymerization reaction of the aliphatic polycarbonate resin A is preferably carried out in a pressure vessel. The content ratio of the ether structural unit in the aliphatic polycarbonate resin A and the molecular weight of the aliphatic polycarbonate resin A can be adjusted by changing the amount of the polymerization catalyst used, the pressure of carbon dioxide, the polymerization temperature, the polymerization time, etc. in the polymerization reaction.

[0101] The amount of the polymerization catalyst used is preferably 0.1 to 15 mg, particularly preferably 0.1 to 10 mg, and further preferably 0.1 to 2 mg per 1 g of the epoxy monomer, for example, in the case of a DMC catalyst. If the amount of the polymerization catalyst used is reduced, the molecular weight of the aliphatic polycarbonate resin A tends to increase.

[0102] The pressure of carbon dioxide is preferably 0.1 to 10 MPa, more preferably 0.3 to 7.5 MPa, particularly preferably 0.5 to 6 MPa, and further preferably 0.7 to 5 MPa. As the pressure of carbon dioxide increases, the content ratio of the carbonate structural unit in the aliphatic polycarbonate resin A tends to increase.

[0103] The amount of carbon dioxide introduced into the aliphatic polycarbonate resin A (CO2 introduction rate) is preferably 10% by mass or more, particularly preferably 15% by mass or more, and further preferably 20% by mass or more. The calculation method of the CO2 introduction rate is shown in the test examples described below.

[0104] The polymerization temperature is preferably -15 to 95° C., particularly preferably 0 to 75° C., and further preferably 25 to 70° C. When the polymerization temperature is increased, the content ratio of the ether structural unit can be increased and the polymerization time can be shortened.

[0105] The polymerization time is preferably 1 to 48 hours, particularly preferably 2 to 30 hours, and further preferably 5 to 24 hours. When the polymerization time is prolonged within this range, the molecular weight of the aliphatic polycarbonate resin A tends to increase.

[0106] The polymerization method may be either solution polymerization or bulk polymerization. As the solvent (polymerization solvent) for implementing solution polymerization, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and vinyl chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; carbonates such as dimethyl carbonate and ethylene carbonate; cellosolve solvents such as ethyl cellosolve, etc. can be used.

[0107] The aliphatic polycarbonate resin A described above can be suitably used as an adhesive. The adhesive may be composed of the aliphatic polycarbonate resin A alone, or may contain the aliphatic polycarbonate resin A and components other than the aliphatic polycarbonate resin A.

[0108] The adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above adhesive has an adhesive force to stainless steel (SUS304, 360 mesh polishing), preferably 1N / 25mm or more, more preferably 5N / 25mm or more, particularly preferably 7N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. On the other hand, the upper limit of the above adhesive force is not particularly limited, but when further considering the need for reprocessability, it is preferably 45N / 25mm or less, particularly preferably 40N / 25mm or less, and further preferably 30N / 25mm or less.

[0109] The adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above adhesive has an adhesive force to polycarbonate of preferably 3N / 25mm or more, more preferably 5N / 25mm or more, particularly preferably 7N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. On the other hand, the upper limit of the above adhesive force is not particularly limited, but when further considering the need for reprocessability, it is preferably 40N / 25mm or less, particularly preferably 30N / 25mm or less, and further preferably 25N / 25mm or less.

[0110] The adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above-mentioned adhesive has an adhesive force to polypropylene, preferably 0.1N / 25mm or more, more preferably 1N / 25mm or more, particularly preferably 3N / 25mm or more, and further preferably 5N / 25mm or more, according to the following limit. On the other hand, the upper limit of the above-mentioned adhesive force is not particularly limited, but when further considering the need for reprocessability, it is preferably 25N / 25mm or less, particularly preferably 20N / 25mm or less, and further preferably 15N / 25mm or less.

[0111] In addition, the specific test method of the adhesive force in this specification is shown in the test example mentioned later.

[0112] The holding force of the adhesive sheet having the adhesive layer (thickness: 25 μm) composed of the above-mentioned adhesive according to JIS Z0237: 2009 (the adherend is set to stainless steel (SUS304, 360 mesh polishing), the attachment area is set to 25 mm × 25 mm, the temperature during the test is set to 40°C, and the load of 9.8N is applied, and the time until the adhesive sheet falls off (maximum 70000 seconds)) (seconds) is preferably 1000 seconds or more, more preferably 2000 seconds or more, particularly preferably 3000 seconds or more, and further preferably 4000 seconds or more. In addition, the specific test method of the holding force in this specification is shown in the test example described later.

[0113] [Aliphatic polycarbonate resin cross-linked product]

[0114] The aliphatic polycarbonate resin crosslinked product of one embodiment of the present invention (hereinafter sometimes referred to as "aliphatic polycarbonate resin crosslinked product B") is a crosslinked product formed by crosslinking the aliphatic polycarbonate resin A of the above-mentioned embodiment. The aliphatic polycarbonate resin crosslinked product B maintains the same low glass transition temperature (Tg) as the aliphatic polycarbonate resin A and exhibits flexibility and tackiness, but due to its crosslinked structure, the cohesive force becomes higher and is more suitable as an adhesive.

[0115] The crosslinking of the aliphatic polycarbonate resin A may be carried out by using a desired crosslinking agent, but self-crosslinking is preferred. That is, the aliphatic polycarbonate resin crosslinked product B of this embodiment is preferably: the crosslinkable functional group (R in formula (Ic) and formula (Id)) possessed by the side chain of the aliphatic polycarbonate resin A is 3 and R 4 The crosslinkable functional groups possessed by the aliphatic polycarbonate resins react with each other to form a crosslinked product by crosslinking a plurality of aliphatic polycarbonate resins A via the crosslinkable functional groups.

[0116] The aliphatic polycarbonate resin crosslinked product B can be suitably prepared by irradiating an aliphatic polycarbonate resin A with energy rays. By irradiating the aliphatic polycarbonate resin A with energy rays, crosslinkable functional groups in the side chains react with each other to form a crosslinked structure.

[0117] Here, energy rays refer to energy rays having energy quanta among electromagnetic waves or charged particle beams, and specific examples thereof include ultraviolet rays, electron beams, etc. Among energy rays, ultraviolet rays are particularly preferred because they are easy to handle.

[0118] The ultraviolet irradiation can be carried out by using a high pressure mercury lamp, an electrodeless lamp, an LED lamp, a xenon lamp, etc. The ultraviolet irradiation amount is preferably 50 to 1000 mW / cm 2 In addition, the light intensity is preferably 50~10000mJ / cm 2 , more preferably 80~5000mJ / cm 2 , particularly preferably 200~2000mJ / cm 2 On the other hand, the electron beam irradiation can be performed using an electron beam accelerator or the like, and the electron beam irradiation dose is preferably about 10 to 1000 krad.

[0119] When ultraviolet rays are used as energy rays for crosslinking the aliphatic polycarbonate resin A, a photopolymerization initiator is preferably added to the aliphatic polycarbonate resin A. By adding a photopolymerization initiator in this way, the aliphatic polycarbonate resin A can be efficiently crosslinked, and the crosslinking time and energy ray irradiation amount can be reduced.

[0120] Examples of such photopolymerization initiators include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinyl-propane-1-one, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2 -methyl anthraquinone, 2-ethyl anthraquinone, 2-tert-butyl anthraquinone, 2-amino anthraquinone, 2-methyl thioxanthone, 2-ethyl thioxanthone, 2-chloro thioxanthone, 2,4-dimethyl thioxanthone, 2,4-diethyl thioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone], (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, phenyl(2,4,6-trimethylbenzoyl)lithium phosphate, etc. These photopolymerization initiators may be used alone or in combination of two or more.

[0121] The amount of the photopolymerization initiator blended is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, particularly preferably 1 parts by mass or more, and further preferably 1.3 parts by mass or more, relative to 100 parts by mass of the aliphatic polycarbonate resin A. In addition, the amount of the photopolymerization initiator blended is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, particularly preferably 5 parts by mass or less, and further preferably 3 parts by mass or less.

[0122] The gel fraction of the aliphatic polycarbonate resin crosslinked product B is preferably 15% or more, more preferably 20% or more, particularly preferably 30% or more, and further preferably 40% or more. Thus, as an adhesive, excellent cohesive force is exerted. In addition, the gel fraction is preferably 85% or less, more preferably 80% or less, particularly preferably 75% or less, and further preferably 70% or less. Thus, softness can be ensured and good adhesive force can be maintained.

[0123] The glass transition temperature (Tg) of the aliphatic polycarbonate resin crosslinked product B is preferably 5°C or less, more preferably -10°C or less, particularly preferably -20°C or less, and further preferably -30°C or less. As a result, the flexibility is excellent and the viscosity becomes better. The aliphatic polycarbonate resin crosslinked product B has a structure formed by crosslinking the aliphatic polycarbonate resin A having the above-mentioned structure, and can achieve the above-mentioned low glass transition temperature (Tg).

[0124] The glass transition temperature (Tg) of the aliphatic polycarbonate resin crosslinked product B is preferably -60°C or higher, more preferably -55°C or higher, particularly preferably -50°C or higher, and further preferably -45°C or higher. This further improves the cohesive force.

[0125] The 5% weight loss temperature of the aliphatic polycarbonate resin crosslinked product B is preferably 200°C or higher, more preferably 210°C or higher, particularly preferably 220°C or higher, and further preferably 230°C or higher. As a result, the aliphatic polycarbonate resin crosslinked product B has excellent heat resistance and can also be suitably used as an adhesive used at high temperatures. The upper limit of the 5% weight loss temperature of the aliphatic polycarbonate resin crosslinked product B is not particularly limited, but is generally preferably 450°C or lower, more preferably 400°C or lower, particularly preferably 350°C or lower, and further preferably 300°C or lower.

[0126] The aliphatic polycarbonate resin crosslinked product B described above can be suitably used as an adhesive. The adhesive may be composed of only the aliphatic polycarbonate resin crosslinked product B, or may contain the aliphatic polycarbonate resin crosslinked product B and components other than the aliphatic polycarbonate resin crosslinked product B. In addition, the adhesive may contain a photopolymerization initiator or a decomposition product thereof.

[0127] The adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above adhesive has an adhesive force to stainless steel (SUS304, 360 mesh polishing), preferably 1N / 25mm or more, more preferably 3N / 25mm or more, particularly preferably 5N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. On the other hand, the upper limit of the above adhesive force is not particularly limited, but when further considering the need for reprocessability, it is preferably 30N / 25mm or less, particularly preferably 25N / 25mm or less, and further preferably 20N / 25mm or less.

[0128] The adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above adhesive has an adhesive force to polycarbonate of preferably 1 N / 25 mm or more, more preferably 2 N / 25 mm or more, particularly preferably 5 N / 25 mm or more, and further preferably 10 N / 25 mm or more, according to the following limit. On the other hand, the upper limit of the above adhesive force is not particularly limited, but when further considering the need for reprocessability, it is preferably 35 N / 25 mm or less, particularly preferably 30 N / 25 mm or less, and further preferably 25 N / 25 mm or less.

[0129] The adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above-mentioned adhesive has an adhesive force to polypropylene, preferably 1N / 25mm or more, more preferably 3N / 25mm or more, particularly preferably 5N / 25mm or more, and further preferably 7N / 25mm or more, according to the following limit. On the other hand, the upper limit of the above-mentioned adhesive force is not particularly limited, but when further considering the need for reprocessability, it is preferably 25N / 25mm or less, particularly preferably 20N / 25mm or less, and further preferably 15N / 25mm or less.

[0130] The holding force of an adhesive sheet having an adhesive layer (thickness: 25 μm) composed of the above-mentioned adhesive according to JIS Z0237: 2009 (the adherend is set to stainless steel (SUS304, 360 mesh polishing), the attachment area is set to 25 mm×25 mm, the temperature during the test is set to 40°C, and a load of 9.8 N is applied, and the time (maximum 70,000 seconds) until the adhesive sheet falls off) (seconds) is preferably 8,000 seconds or more, more preferably 10,000 seconds or more, particularly preferably 30,000 seconds or more, and further preferably 70,000 seconds or more.

[0131] The aliphatic polycarbonate resin A and the aliphatic polycarbonate resin crosslinked product B described above can be used for adhesives, adhesives, coating agents, etc. due to the flexibility brought about by their low glass transition temperature (Tg). In addition, the aliphatic polycarbonate resin A and the aliphatic polycarbonate resin crosslinked product B can be particularly suitably used as an adhesive due to their tackiness. For example, they can be used for attaching labels to various containers, daily necessities, electrical and electronic equipment, various machines, medical instruments, etc., and for bonding components to each other.

[0132] [Adhesive sheet]

[0133] Hereinafter, embodiments of the adhesive sheet of the present invention will be described.

[0134] The adhesive sheet of the first embodiment of the present invention has an adhesive layer composed of an adhesive, the adhesive containing 50% by mass or more of an aliphatic polycarbonate resin having an ether structure on the main chain and a crosslinkable functional group on the side chain (hereinafter sometimes referred to as "aliphatic polycarbonate resin A0"), and the adhesive force of the adhesive sheet to polypropylene is 1.5N / 25mm or more. In addition, the specific test method of the adhesive force in this specification is shown in the test examples described later.

[0135] In addition, the adhesive sheet of the second embodiment of the present invention has an adhesive layer composed of an adhesive, the adhesive containing 50% by mass or more of an aliphatic polycarbonate resin crosslinked product (hereinafter sometimes referred to as "aliphatic polycarbonate resin crosslinked product B0"), the aliphatic polycarbonate resin crosslinked product is a crosslinked product of an aliphatic polycarbonate resin having an ether structure on the main chain and a crosslinkable functional group on the side chain (aliphatic polycarbonate resin A0), and the adhesive force of the adhesive sheet to polypropylene is 1.5N / 25mm or more.

[0136] For the adhesive sheet of the first embodiment, by making the adhesive layer composed of an adhesive containing 50% or more of the above-mentioned aliphatic polycarbonate resin A0, and having the above-mentioned adhesive force, both high-polarity materials and low-polarity materials have good adhesive force, and the holding force is also excellent. In addition, for the adhesive sheet of the second embodiment, by making the adhesive layer composed of an adhesive containing 50% or more of the above-mentioned aliphatic polycarbonate resin crosslinked product B0, and having the above-mentioned adhesive force, both high-polarity materials and low-polarity materials have good adhesive force, and the holding force is also excellent. In particular, the above-mentioned aliphatic polycarbonate resin crosslinked product B0 is formed by crosslinking the above-mentioned aliphatic polycarbonate resin A0, and has good cohesive force, and the adhesive force and holding force are more excellent.

[0137] The aliphatic polycarbonate resin A0 and the aliphatic polycarbonate resin crosslinked product B0 can be produced using carbon dioxide as a raw material as described below. Therefore, the adhesive sheets of the first and second embodiments can achieve effective use of carbon dioxide during production.

[0138] Among them, as high-polarity materials (materials having a high-polarity surface), for example, metals such as stainless steel, aluminum, and copper; glass; resins such as polycarbonate resins, acrylic resins, and polyethylene terephthalate resins, etc. In addition, as low-polarity materials (materials having a low-polarity surface), for example, polyolefin resins such as polyethylene and polypropylene, polyacetal resins, and polytetrafluoroethylene resins can be listed.

[0139] The adhesive strength of the adhesive sheet of the first embodiment to polypropylene is, according to the following limit, 1.5 N / 25 mm or more, preferably 3 N / 25 mm or more, particularly preferably 5 N / 25 mm or more, and further preferably 7 N / 25 mm or more. On the other hand, the upper limit of the above-mentioned adhesive strength is not particularly limited, but in further consideration of the need for reprocessability, it is preferably 25 N / 25 mm or less, particularly preferably 20 N / 25 mm or less, and further preferably 15 N / 25 mm or less.

[0140] The adhesion of the adhesive sheet of the first embodiment to stainless steel (SUS304, 360 mesh polishing) is preferably 1N / 25mm or more, more preferably 5N / 25mm or more, particularly preferably 7N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. According to the adhesive sheet of the first embodiment, it is possible to exert good adhesion to high-polarity materials as described above. On the other hand, the upper limit of the above-mentioned adhesion is not particularly limited, but when further considering the need for reprocessability, it is preferably 45N / 25mm or less, particularly preferably 40N / 25mm or less, and further preferably 30N / 25mm or less.

[0141] The adhesion of the adhesive sheet of the first embodiment to polycarbonate is preferably 3N / 25mm or more, more preferably 5N / 25mm or more, particularly preferably 7N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. According to the adhesive sheet of the first embodiment, it is possible to exert good adhesion to high-polarity materials as described above. On the other hand, the upper limit of the above-mentioned adhesion is not particularly limited, but when further considering the need for reprocessability, it is preferably 40N / 25mm or less, particularly preferably 30N / 25mm or less, and further preferably 25N / 25mm or less.

[0142] The holding force of the adhesive sheet of the first embodiment according to JIS Z0237: 2009 (the time (maximum 70,000 seconds) until the adhesive sheet falls off when the adherend is set to stainless steel (SUS304, 360 mesh polishing), the attachment area is set to 25 mm×25 mm, the temperature during the test is set to 40°C, and a load of 9.8N is applied) (seconds) is preferably 1,000 seconds or more, more preferably 2,000 seconds or more, particularly preferably 3,000 seconds or more, and further preferably 4,000 seconds or more. According to the adhesive sheet of the first embodiment, it is possible to exert excellent holding force as described above. In addition, the specific test method of the holding force in this specification is shown in the test examples described later.

[0143] The adhesive strength of the adhesive sheet of the second embodiment to polypropylene is, according to the following limit, 1.5 N / 25 mm or more, preferably 3 N / 25 mm or more, particularly preferably 5 N / 25 mm or more, and further preferably 7 N / 25 mm or more. On the other hand, the upper limit of the above-mentioned adhesive strength is not particularly limited, but in further consideration of the need for reprocessability, it is preferably 25 N / 25 mm or less, particularly preferably 20 N / 25 mm or less, and further preferably 15 N / 25 mm or less.

[0144] The adhesive sheet of the second embodiment has an adhesive force to stainless steel (SUS304, 360 mesh polishing), preferably 1N / 25mm or more, more preferably 3N / 25mm or more, particularly preferably 5N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. According to the adhesive sheet of the second embodiment, it is possible to exert good adhesion to high-polarity materials as described above. On the other hand, the upper limit of the above-mentioned adhesion is not particularly limited, but when further considering the need for reprocessability, it is preferably 30N / 25mm or less, particularly preferably 25N / 25mm or less, and further preferably 20N / 25mm or less.

[0145] The adhesive sheet of the second embodiment has an adhesion to polycarbonate, preferably 1N / 25mm or more, more preferably 2N / 25mm or more, particularly preferably 5N / 25mm or more, and further preferably 10N / 25mm or more, according to the following limit. According to the adhesive sheet of the second embodiment, it is possible to exert good adhesion to high-polarity materials as described above. On the other hand, the upper limit of the above-mentioned adhesion is not particularly limited, but when further considering the need for reprocessability, it is preferably 35N / 25mm or less, particularly preferably 30N / 25mm or less, and further preferably 25N / 25mm or less.

[0146] The holding force of the adhesive sheet of the second embodiment according to JIS Z0237:2009 (the adherend is set to stainless steel (SUS304, 360 mesh polishing), the attachment area is set to 25mm×25mm, the temperature during the test is set to 40°C, and a load of 9.8N is applied, and the time until the adhesive sheet falls off (maximum 70,000 seconds)) (seconds) is preferably 8,000 seconds or more, more preferably 10,000 seconds or more, particularly preferably 30,000 seconds or more, and further preferably 70,000 seconds or more. According to the adhesive sheet of the second embodiment, it is possible to exert excellent holding force as described above.

[0147] 1. Adhesive

[0148] (1) Adhesive in the First Embodiment

[0149] The adhesive constituting the adhesive layer in the adhesive sheet of the first embodiment contains 50% by mass or more of an aliphatic polycarbonate resin A0 having an ether structure in the main chain and a crosslinkable functional group in the side chain. The aliphatic polycarbonate resin A0 is preferably the aliphatic polycarbonate resin A in the above-mentioned embodiment.

[0150] The aliphatic polycarbonate resin A0 is preferably a polymerization product of carbon dioxide and epoxide. Specifically, the aliphatic polycarbonate resin A0 can be prepared in the same manner as the aliphatic polycarbonate resin A described above.

[0151] The adhesive in the first embodiment contains 50% by mass or more, preferably 60% by mass or more, particularly preferably 70% by mass or more, and further preferably 80% by mass or more of the aliphatic polycarbonate resin A0. The upper limit of the content is not particularly limited and may be 100% by mass.

[0152] The adhesive in the first embodiment may also contain components other than the aliphatic polycarbonate resin A0. Such components include, for example, various additives known in the adhesive field, such as tackifiers, ultraviolet absorbers, dyes, pigments, antioxidants, anti-degradation agents, antistatic agents, flame retardants, light stabilizers, softeners, silane coupling agents, and fillers.

[0153] (2) Adhesive in the Second Embodiment

[0154] The adhesive constituting the adhesive layer in the adhesive sheet of the second embodiment contains 50% by mass or more of an aliphatic polycarbonate resin crosslinked product B0, which is a crosslinked product of an aliphatic polycarbonate resin A0 having an ether structure in the main chain and a crosslinkable functional group in the side chain. The aliphatic polycarbonate resin crosslinked product B0 is preferably a crosslinked product of an aliphatic polycarbonate resin A having the aforementioned structure SA (aliphatic polycarbonate resin crosslinked product B), and is particularly preferably a self-crosslinked product of an aliphatic polycarbonate resin A having the aforementioned structure SA.

[0155] The aliphatic polycarbonate resin crosslinked product B, which is a crosslinked product of the aliphatic polycarbonate resin A having the structure SA, maintains a low glass transition temperature (Tg) like the aliphatic polycarbonate resin A having the structure SA, thereby exhibiting flexibility and tackiness, but due to its crosslinked structure, the cohesive force becomes higher, and the adhesive force and holding power become more excellent.

[0156] The aliphatic polycarbonate resin crosslinked product B0 may be a crosslinked product formed by crosslinking an aliphatic polycarbonate resin A0 using a desired crosslinking agent, but is preferably a crosslinked product formed by self-crosslinking an aliphatic polycarbonate resin A0, and is particularly preferably a crosslinked product formed by self-crosslinking an aliphatic polycarbonate resin A having a structure SA. Specifically, it is preferably formed by crosslinking the crosslinkable functional group (R in formula (Ic) and formula (Id)) possessed by the side chain of the aliphatic polycarbonate resin A 3 and R 4 The crosslinkable functional groups possessed by the aliphatic polycarbonate resins react with each other to form a crosslinked product by crosslinking a plurality of aliphatic polycarbonate resins A via the crosslinkable functional groups.

[0157] The aliphatic polycarbonate resin crosslinked product B0 can be suitably prepared by irradiating the aliphatic polycarbonate resin A0 with energy rays. Specifically, the aliphatic polycarbonate resin crosslinked product B0 can be prepared in the same manner as the aliphatic polycarbonate resin crosslinked product B described above.

[0158] The adhesive in the second embodiment contains 50% by mass or more, preferably 60% by mass or more, particularly preferably 70% by mass or more, and more preferably 80% by mass or more of the aliphatic polycarbonate resin B. The upper limit of the content is not particularly limited, and may be 100% by mass.

[0159] The adhesive in the second embodiment may contain components other than the aliphatic polycarbonate resin B. Examples of such components include various additives known in the adhesive field, such as a photopolymerization initiator or its decomposition product, a tackifier, an ultraviolet absorber, a dye, a pigment, an antioxidant, an anti-degradation agent, an antistatic agent, a flame retardant, a light stabilizer, a softener, a silane coupling agent, and a filler.

[0160] 2. Adhesive layer

[0161] From the viewpoint of adhesive force and holding force, the thickness of the adhesive layer in the adhesive sheet of the first and second embodiments (value measured according to JIS K7130) is preferably 1 μm or more, more preferably 5 μm or more, particularly preferably 10 μm or more, and further preferably 20 μm or more, based on the following limit values.

[0162] From the viewpoint of coating properties and handling properties, the thickness of the adhesive layer is preferably 80 μm or less, more preferably 50 μm or less, particularly preferably 40 μm or less, and further preferably 30 μm or less, as the upper limit.

[0163] 3. Configuration example

[0164] The specific structure of an example of the adhesive sheet of the first and second embodiments is shown in Figure 1 and Figure 2 .

[0165] like Figure 1 As shown, an adhesive sheet 1A according to one embodiment includes, in order from the bottom, a release sheet 12 , an adhesive layer 11 laminated on the release surface of the release sheet 12 , and a base material 13 laminated on the adhesive layer 11 .

[0166] In addition, if Figure 2 As shown, the adhesive sheet 1B of another embodiment is composed of two release sheets 12a, 12b and an adhesive layer 11, and the adhesive layer 11 is sandwiched by the two release sheets 12a, 12b in a manner of contacting the release surfaces of the two release sheets 12a, 12b. In addition, the release surface of the release sheet in this specification refers to the surface of the release sheet that has release properties, including both the surface that has been subjected to a release treatment and the surface that exhibits release properties even if a release treatment is not applied.

[0167] 3-1. Each element

[0168] (1)Adhesive layer

[0169] As described above, the adhesive layer 11 in the present embodiment is composed of an adhesive containing 50% by mass or more of the aliphatic polycarbonate resin A, or an adhesive containing 50% by mass or more of the aliphatic polycarbonate resin crosslinked product B.

[0170] (2) Peel sheet

[0171] The release sheets 12, 12a, 12b protect the adhesive layer 11 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheets 1A, 1B (adhesive layer 11) are used. In the adhesive sheets 1A, 1B of this embodiment, one or both of the release sheets 12, 12a, 12b are not essential.

[0172] As the release sheets 12, 12a, 12b, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene-(meth)acrylic acid copolymer film, ethylene-(meth)acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film and other plastic films, cross-linked films of these films, etc., and papers such as high-quality paper, glass paper, kraft paper, claycoated paper, etc. can be used. Furthermore, laminates of these materials can also be used.

[0173] The release surfaces of the release sheets 12, 12a, 12b (especially the surface in contact with the adhesive layer 11) are preferably subjected to a release treatment. Examples of release agents used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents. In addition, one of the release sheets 12a and 12b may be a heavy release type release sheet with a larger release force, and the other release sheet may be a light release type release sheet with a smaller release force.

[0174] The thickness of the release sheets 12 , 12 a , and 12 b is not particularly limited, but is generally about 20 to 150 μm.

[0175] (3) Base material

[0176] The substrate 13 is not particularly limited, and a conventional sheet material used as a substrate sheet of an adhesive sheet can be used. For example, the following can be cited: the required optical components, and woven fabrics or non-woven fabrics using fibers such as polyester, acrylic, and rayon; synthetic paper; papers such as high-quality paper, glassine, impregnated paper, and coated paper; metal foils such as aluminum and copper; foams such as urethane foam and polyethylene foam; polyester films such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene succinate, and polybutylene terephthalate-adipate (composite); polyurethane films; polyethylene films; polypropylene films; cellulose films such as triacetyl cellulose; polyvinyl chloride films; polyvinylidene chloride films; polyvinyl alcohol films; ethylene-vinyl acetate copolymer films; polystyrene films; polycarbonate films; acrylic resin films; norbornene resin films; cycloolefin resin films; and laminates of two or more of the above materials. Plastic films can be stretched uniaxially or biaxially.

[0177] The thickness of the substrate 13 varies depending on its type, but is generally 10 to 150 μm, preferably 20 to 100 μm, and particularly preferably 25 to 75 μm.

[0178] 3-2. Manufacturing method

[0179] When manufacturing the adhesive sheet 1A of the first embodiment, it is preferred that an adhesive solution (coating solution) containing aliphatic polycarbonate resin A is applied to the release surface of the release sheet 12 and heat treated to form the adhesive layer 11 , and then the substrate 13 is laminated on the adhesive layer 11 .

[0180] In addition, when manufacturing the adhesive sheet 1B of the first embodiment, it is preferred that: a solution of an adhesive containing aliphatic polycarbonate resin A (coating solution) is coated on the release surface of a release sheet 12a (or 12b), and a heat treatment is performed to form an adhesive layer 11, and then the release surface of another release sheet 12b (or 12a) is superimposed on the adhesive layer 11.

[0181] On the other hand, when manufacturing the adhesive sheet 1A of the second embodiment, it is preferred that: a solution of an adhesive containing an aliphatic polycarbonate resin A (coating solution) is coated on the release surface of the release sheet 12, and after heat treatment, a substrate 13 is laminated on the coating layer, and finally the coating layer is irradiated with energy rays to crosslink the coating layer, thereby forming the adhesive layer 11. The irradiation with energy rays can be performed, for example, through the release sheet 12.

[0182] In addition, when manufacturing the adhesive sheet 1B of the second embodiment, it is preferred that: a solution (coating solution) of an adhesive containing aliphatic polycarbonate resin A is applied to the release surface of one release sheet 12a (or 12b), and after heat treatment, the release surface of another release sheet 12b (or 12a) is superimposed on the coating layer, and finally the coating layer is irradiated with energy rays to crosslink the coating layer, thereby forming the adhesive layer 11. The irradiation with energy rays can be performed via the desired release sheet (12a or 12b).

[0183] As the diluting solvent for diluting the above-mentioned adhesive to make it into a coating solution, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and 1,2-dichloroethane; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-based solvents such as ethyl cellosolve, etc. can be used.

[0184] As the concentration and viscosity of the coating solution prepared in the above manner, as long as it is within the range that can be coated, there is no particular restriction and it can be appropriately selected as appropriate. For example, dilution is performed in a manner such that the concentration of the adhesive is 10 to 40% by mass. In addition, when obtaining the coating solution, the addition of a diluting solvent or the like is not a necessary condition, and as long as the adhesive is a viscosity that can be coated, a diluting solvent may not be added. In this case, the adhesive is directly used as the coating solution.

[0185] As a method for applying the coating solution, for example, a bar coating method, a knife coating method, a comma coating method, a roll coating method, a blade coating method, a die coating method, a gravure coating method, or the like can be utilized.

[0186] The coating film of the coating solution is subjected to a heating treatment to volatilize the dilution solvent, thereby forming an adhesive layer (or coating layer). The heating conditions are, for example, preferably 30 to 120° C. for 1 to 10 minutes, and particularly preferably 100 to 120° C. for 1 to 5 minutes.

[0187] 4. Application of adhesive sheet

[0188] The adhesive sheets of the first and second embodiments can be used, for example, for attaching labels to various containers, daily necessities, electrical and electronic equipment, various machines, medical instruments, etc., for laminating members together, and the like.

[0189] The material of the adherend is not particularly limited, and can be, for example, metals such as stainless steel, aluminum, and copper; glass; high-polarity materials such as resins such as polycarbonate resin, acrylic resin, and polyethylene terephthalate resin; polyolefin resins such as polyethylene and polypropylene, and low-polarity materials such as polyacetal and polytetrafluoroethylene.

[0190] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes and equivalents within the technical scope of the present invention.

[0191] For example, the release sheet 12 of the adhesive sheet 1A may be omitted, or any one of the release sheets 12a and 12b of the adhesive sheet 1B may be omitted.

[0192] Example

[0193] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.

[0194] [Example 1]

[0195] (1) Synthesis of polymerization catalyst

[0196] 1.33 g of potassium cobalt cyanide (K3[Co(CN)6]; manufactured by FUJIFILM Wako Pure Chemical Corporation) was dissolved in 20 mL of deionized water and added dropwise to a 50°C zinc chloride solution (a solution obtained by dissolving 11.42 g of ZnCl2 in a mixed solution of 60 mL of deionized water and 30 mL of tert-butyl alcohol) that was vigorously stirred for 45 minutes. Thereafter, the mixture was vigorously stirred for 60 minutes. The obtained white suspension was centrifuged at 5000 rpm to separate a white solid. The separated white solid was resuspended in a solution of tert-butyl alcohol and deionized water (tert-butyl alcohol: deionized water = 5:5 by volume) while being vigorously stirred for 30 minutes. Thereafter, the amount of tert-butyl alcohol was gradually increased in water (the volume ratio of tert-butyl alcohol: deionized water was changed from 6:4 to 7:3, 8:2, and 9:1), and separation and resuspension by centrifugation were repeated several times. Finally, the white solid was resuspended in tert-butyl alcohol and separated by centrifugation, and then dried at 50° C. under vacuum to a predetermined mass, thereby obtaining Zn 3 (Co [CN] 6) 2 as a DMC catalyst.

[0197] (2) Synthesis of polymers

[0198] As raw material monomers, 1,2-epoxydecane (Edec; 1,2-decene epoxide) as epoxide E1 and 4-hydroxybutyl acrylate glycidyl ether (4HBAGE; manufactured by Mitsubishi Chemical Corporation) as epoxide E2 were prepared. Next, 1,2-epoxydecane and 4-hydroxybutyl acrylate glycidyl ether were blended at a ratio (molar ratio) of 99:1 and diluted with 50 parts by mass of toluene (dehydrated toluene (manufactured by KANTO CHEMICAL CO., INC., with a purity of 99.5% or more as confirmed by GC) as a polymerization solvent.

[0199] The two components were added to a pressure vessel at a ratio of 1 g of the raw monomers (total, excluding the solvent) to 1 mg of the DMC catalyst obtained in (1). In addition, 200 ppm of phenothiazine (manufactured by Tokyo Chemical Industry Co., Ltd., with a purity of 99.5% or more as confirmed by GC) was added as a polymerization inhibitor. Then, stirring was performed under an argon atmosphere.

[0200] Next, the interior of the pressure vessel was purged with CO 2 , and then CO 2 was introduced into the pressure vessel by an infusion pump to set the pressure in the pressure vessel to 4 MPa. Next, the mixture was stirred at 60° C. for 18 hours to carry out a polymerization reaction.

[0201] After the reaction is completed, toluene is added to the contents in the pressure vessel to prepare a solution, and the solution is added dropwise to methanol to which 1M hydrochloric acid is added, thereby reprecipitating and purifying. The obtained precipitate is recovered by filter paper and dissolved in chloroform, and then impurities are removed by a membrane filter (manufactured by Adbandek Toyo Co., Ltd., with a pore size of 3.00 μm). Afterwards, the solution is injected into a Teflon (registered trademark) dish and dried in a drying oven at 50° C. for 20 hours to obtain a polymer.

[0202] pass 1 The structure of the obtained polymer (aliphatic polycarbonate resin) was confirmed by H-NMR (apparatus: manufactured by Bruker Corporation, product name "Biospin Avance 500"). Figure 3 In addition, in the obtained aliphatic polycarbonate resin, R in the aforementioned formula (Ia) to formula (Id) 1 and R 2 -C8H 17 , R 3 and R 4It is -CO-(CH2)4-OC(=O)-CH=CH2.

[0203] According to the above results, the ratio of the ether structural unit to the carbonate unit was estimated by the integral ratio of the methylene hydrogen corresponding to each of the ether structural unit and the carbonate unit. As a result, the ratio (content) of the ether structural unit in the obtained aliphatic polycarbonate resin was 1.6%, and the carbonate ratio (content) was 98.4%. In addition, the ratio of the ether structural unit was calculated by the following calculation formula according to α, β, γ in the chart.

[0204] Ether structural unit ratio [%] = {γ / (α+β+γ)} × 100

[0205] (3) Manufacturing of adhesive sheets

[0206] The aliphatic polycarbonate resin obtained above was dissolved in ethyl acetate, and 1.5 parts by mass of 1-hydroxycyclohexyl phenyl ketone as a photopolymerization initiator was added to 100 parts by mass (solid content conversion value; the same applies hereinafter) of the aliphatic polycarbonate resin, and the mixture was stirred thoroughly to prepare a coating liquid for an adhesive.

[0207] The coating liquid of the above-mentioned adhesive was applied to the release-treated surface of a release sheet (manufactured by LINTEC Corporation, product name "SP-PET381031") on which one side of a polyethylene terephthalate film was subjected to release treatment with a silicone release agent. Next, the coating layer was heated at 100°C for 1 minute to form an adhesive layer with a thickness of 25 μm. Next, the adhesive layer on the release sheet was bonded to a polyethylene terephthalate film (manufactured by TOYOBO CO., LTD., product name "COSMOSHINE A4360", thickness of 50 μm) as a substrate, and this was used as an adhesive sheet (before UV; equivalent to the adhesive sheet of the first embodiment).

[0208] The thickness of the adhesive layer is a value measured using a constant pressure thickness gauge (manufactured by Teclock Co., Ltd., product name "PG-02") in accordance with JIS K7130.

[0209] Next, the adhesive sheet is irradiated with energy rays (ultraviolet rays) through the release sheet under the following conditions to crosslink the adhesive layer. In addition, the crosslinked adhesive layer is composed of aliphatic polycarbonate resin crosslinked material. The adhesive sheet having the crosslinked adhesive layer is referred to as an adhesive sheet (after UV; equivalent to the adhesive sheet of the second embodiment).

[0210] <Energy ray irradiation conditions>

[0211] Use high pressure mercury lamp

[0212] Illuminance: 200mW / cm 2 , light intensity is 1800mJ / cm 2

[0213] ・The UV illuminance meter used was "UVPF-A1" manufactured by EYE GRAPHICS COMPANY

[0214] [Examples 2 to 6]

[0215] The polymer and adhesive sheet were manufactured in the same manner as in Example 1, except that the blending ratio (molar ratio) of 1,2-decene oxide and 4-hydroxybutyl acrylate glycidyl ether was changed to 99.5:0.5 (Example 2), 99.7:0.3 (Example 3), 99.9:0.1 (Example 4), 99.5:0.5 (bulk polymerization was adopted without using a polymerization solvent, CO2 pressure: 1 MPa) (Example 5), and 99.5:0.5 (CO2 pressure: 1 MPa) (Example 6).

[0216] pass 1 The structure of the obtained polymer (aliphatic polycarbonate resin) was confirmed by H-NMR (apparatus: manufactured by Bruker Corporation, product name "Biospin Avance 500"). Table 1 shows the ratio of ether structural units and the ratio of carbonate in the aliphatic polycarbonate resin.

[0217] [Examples 7 to 10]

[0218] As raw material monomers, 1,2-octyl oxide (Eoct; 1,2-octene epoxide) as epoxide E1 and 4-hydroxybutyl acrylate glycidyl ether (4HBAGE; manufactured by Mitsubishi Chemical Corporation) as epoxide E2 were prepared. Next, 1,2-octyl oxide and 4-hydroxybutyl acrylate glycidyl ether were blended at a ratio (molar ratio) of 99.9:0.1 (Example 7), 99.7:0.3 (Example 8), 99.5:0.5 (Example 9), and 99:1 (Example 10).

[0219] A polymer and an adhesive sheet were produced in the same manner as in Example 1 except that the above-mentioned raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. 1 The structure of the obtained polymer (aliphatic polycarbonate resin) was confirmed by H-NMR (apparatus: manufactured by Bruker Corporation, product name "Biospin Avance 500"). Table 1 shows the ratio of ether structural units and the ratio of carbonate in the aliphatic polycarbonate resin.

[0220] [Examples 11 and 12]

[0221] As raw material monomers, 1,2-octyl oxide (Eoct; 1,2-octene epoxide) as epoxide E1 and allyl glycidyl ether (AGE) as epoxide E2 were prepared. Then, 1,2-octyl oxide and allyl glycidyl ether were blended at a ratio (molar ratio) of 99:1 (Example 11) and 90:10 (Example 12).

[0222] A polymer and an adhesive sheet were produced in the same manner as in Example 1 except that the above-mentioned raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. 1 The structure of the obtained polymer (aliphatic polycarbonate resin) was confirmed by H-NMR (apparatus: manufactured by Bruker Corporation, product name "Biospin Avance 500"). Table 1 shows the ratio of ether structural units and the ratio of carbonate in the aliphatic polycarbonate resin.

[0223] [Example 13]

[0224] As raw material monomers, 1,2-epoxydecane (Edec; 1,2-decene epoxide) as epoxide E1 and allyl glycidyl ether (AGE) as epoxide E2 were prepared. Next, 1,2-epoxyoctane and allyl glycidyl ether were blended at a ratio (molar ratio) of 99:10.

[0225] A polymer and an adhesive sheet were produced in the same manner as in Example 1 except that the above-mentioned raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. 1 The structure of the obtained polymer (aliphatic polycarbonate resin) was confirmed by H-NMR (apparatus: manufactured by Bruker Corporation, product name "Biospin Avance 500"). Table 1 shows the ratio of ether structural units and the ratio of carbonate in the aliphatic polycarbonate resin.

[0226] [Comparative Example 1]

[0227] (1) Synthesis of polymerization catalyst

[0228] (R,R)-N,N'-bis(3,5-di-tert-butyl salicylidene)-1,2-cyclohexyldiamine cobalt (II) (manufactured by Sigma-Aldrich Japan, product name "(R,R)-salcyCoⅠⅠ") and pentafluorobenzoic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were weighed in a molar ratio of 1:1.1 and placed in a flask, and dehydrated toluene was added thereto. Then, the beaker was shielded from light with aluminum foil and allowed to react at room temperature for 20 hours. After the reaction was completed, the solvent was removed under reduced pressure and washed several times with excess hexane. After that, vacuum drying was performed at room temperature to obtain a cobalt-salen complex.

[0229] (2) Synthesis of polymers

[0230] 1,2-propylene oxide (propylene oxide; PO) as an epoxy monomer (classified as epoxide E1 for convenience), the cobalt-salen complex obtained in (1) as a polymerization catalyst, and bis(triphenylphosphorane)ammonium chloride (PPNCl) as a cocatalyst were weighed at a molar ratio of epoxy monomer: polymerization catalyst: cocatalyst = 2000: 1: 1, and stirred in a pressure vessel. The above operations were all carried out after replacing the interior of the pressure vessel with an argon atmosphere. In addition, bulk polymerization was adopted in this polymerization process without using a polymerization solvent.

[0231] Next, after the interior of the pressure vessel was purged with CO 2 , CO 2 was introduced into the pressure vessel by an infusion pump, and the pressure in the pressure vessel was set to 1.5 MPa. Next, the mixture was stirred at 23° C. for 5 hours to carry out a polymerization reaction.

[0232] After the reaction is completed, chloroform is added to the contents of the pressure vessel to prepare a chloroform solution, which is concentrated using a rotary evaporator. The concentrated solution is added dropwise to methanol to which 1M hydrochloric acid is added while stirring to precipitate the product. Thereafter, the product is recovered by vacuum filtration using a diaphragm pump. The recovered product is dissolved again in chloroform, and impurities are removed using a membrane filter (manufactured by Adbandec Toyo Co., Ltd., pore size 3.00 μm). Thereafter, the solution is injected into a Teflon (registered trademark) dish, and dried in a drying oven at 50°C for 20 hours to obtain a polymer. By 1 The structure of the polymer (aliphatic polycarbonate resin; the number of carbon atoms in the side chain) was confirmed by H-NMR (apparatus: manufactured by Bruker, product name "Biospin Avance 500"). The obtained graph is shown in Figure 4 .

[0233] According to the above results, the ratio of carbonate unit to ether structural unit was estimated by the integral ratio of methylene hydrogen corresponding to each of carbonate unit and ether structural unit. As a result, no diffraction peak of γ was observed, so the ratio (content; mass basis) of ether structural unit in the obtained aliphatic polycarbonate resin was 0.0%.

[0234] (3) Manufacturing of adhesive sheets

[0235] Using the aliphatic polycarbonate resin obtained above, an adhesive sheet was produced in the same manner as in Example 1. The adhesive layer of the obtained adhesive sheet had no tackiness, and the adhesive force and holding force could not be measured.

[0236] [Comparative Example 2]

[0237] As raw material monomers, 1,2-propylene oxide (propylene oxide; PO) (classified as epoxide E1 for convenience) and 4-hydroxybutyl acrylate glycidyl ether (4HBAGE; manufactured by Mitsubishi Chemical Corporation) as epoxide E2 were prepared. Then, 1,2-propylene oxide and 4-hydroxybutyl acrylate glycidyl ether were blended at a ratio (mass ratio) of 90:10.

[0238] The same operation as in Example 1 was carried out to prepare a polymer, except that the above-mentioned raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. However, gelation occurred, and a polymer whose physical properties could be measured could not be obtained.

[0239] [Test Example 1] <Measurement of number average molecular weight (Mn)>

[0240] The number average molecular weight (Mn) of the aliphatic polycarbonate resins prepared in Examples and Comparative Examples was measured (GPC measurement) under the following conditions using gel permeation chromatography (GPC) and converted to standard polystyrene.

[0241] [Measurement conditions]

[0242] ·GPC measuring apparatus: manufactured by TOSOH CORPORATION, HLC-8320

[0243] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION

[0244] TSK guard column SuperH-H

[0245] TSK gel SuperHM-H

[0246] TSK gel SuperHM-H

[0247] TSK gel SuperH2000

[0248] · Determination solvent: tetrahydrofuran

[0249] ·Measurement temperature: 40℃

[0250] [Test Example 2] <Measurement of glass transition temperature (Tg)>

[0251] The aliphatic polycarbonate resin prepared in the examples and comparative examples (before UV) and the aliphatic polycarbonate crosslinked product (after UV) constituting the adhesive layer of the adhesive sheet (after UV) manufactured in the examples were measured by a differential scanning calorimeter (manufactured by TA Instruments Japan Inc., product name "DSCQ2000") to obtain the glass transition temperature (Tg). Specifically, 4 mg of the polymer test sample was taken, placed in an aluminum pan and sealed with a lid. In a dry nitrogen atmosphere, the test sample was heated / cooled at a heating / cooling rate of 10°C / minute in the range of -70°C to 70°C. The DSC curve was drawn using the data obtained during the second heating. The temperature of the intersection of the baseline on the low temperature side of the obtained DSC curve extended to the straight line on the high temperature side and the tangent drawn at the point where the slope of the curve of the step-like change part of the glass transition is the largest is taken as the glass transition temperature (Tg). The results are shown in Table 1.

[0252] [Test Example 3] <Measurement of Gel Fraction>

[0253] The adhesive sheets (before UV) and adhesive sheets (after UV) manufactured in the examples and comparative examples were cut into a size of 80 mm × 80 mm, and the adhesive layer was wrapped in a polyester net (mesh size 200), and the mass was weighed with a precision balance, and the mass of the net alone was subtracted to calculate the mass of the adhesive alone. The mass at this time was set as M1.

[0254] Next, the adhesive wrapped in the above polyester mesh is immersed in ethyl acetate at room temperature (23°C) for 72 hours. After that, the adhesive is taken out and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and further dried in an oven at 80°C for 12 hours. After drying, its mass is weighed with a precision balance, and the mass of the above mesh alone is subtracted to calculate the mass of the adhesive alone. The mass at this time is set to M2. The gel fraction (%) is expressed by (M2 / M1)×100. Thus, the gel fraction (%) of each adhesive (aliphatic polycarbonate resin (before UV) and aliphatic polycarbonate resin crosslinked product (after UV)) is obtained. The results are shown in Table 1.

[0255] [Test Example 4] <Determination of 5% weight loss temperature>

[0256] The aliphatic polycarbonate resins (before UV) prepared in the examples and comparative examples, and the aliphatic polycarbonate resin crosslinked products (after UV) constituting the adhesive layer of the adhesive sheet (after UV) prepared in the examples were subjected to thermogravimetric measurement (according to JIS K7120 "Thermogravimetric Test Method for Plastics") using a differential thermal thermogravimetric analyzer (manufactured by SHIMADZU CORPORATION, product name "DTG-60"). The flowing gas was nitrogen, and the temperature was raised from 40°C to 550°C at a gas flow rate of 100 ml / min and a heating rate of 20°C / min. Based on the obtained thermogravimetric curve, the temperature (5% weight loss temperature) at which the mass was reduced by 5% relative to the mass at a temperature of 100°C was obtained. The results are shown in Table 1.

[0257] [Test Example 5] <Measurement of Adhesion Strength>

[0258] The adhesive sheets (before UV) and adhesive sheets (after UV) manufactured in the examples and comparative examples were cut into pieces with a width of 25 mm and a length of 300 mm. In an environment of 23°C and 50% RH, the release sheet was peeled off from the above adhesive sheet, and the exposed adhesive layer was attached to the following three adherends. When attaching, a roller weighing 2 kg was rolled back and forth once to press the adhesive sheet onto the adherend. Afterwards, it was placed in an environment of 23°C and 50% RH for 24 hours as a sample for measuring adhesion.

[0259] Next, under an environment of 23°C and 50% RH, a tensile tester (manufactured by ORIENTEC CO., LTD., product name "TENSILON") was used to measure the adhesion (N / 25mm) when the laminate of the base film and the adhesive layer in the sample for measuring the adhesion was peeled off from the adherend at a peeling speed of 300 mm / min and a peeling angle of 180°. The conditions not described here were measured in accordance with JIS Z0237: 2000. The results are shown in Table 1. In addition, for the adherend polypropylene (PP) plate in the adhesive sheet (before UV) of Example 1, there was a difference in adhesion due to the occurrence of zipping. Therefore, as the value of adhesion, the maximum value average and the minimum value average are taken.

[0260] <Adhesive>

[0261] Stainless steel (SUS) plate (SUS304, 360 mesh polishing)

[0262] Polycarbonate (PC) sheet (manufactured by Yuko Shokai Co., Ltd., product name "PC (PC-1600)", thickness: 2 mm)

[0263] Polypropylene (PP) sheet (manufactured by Yuko Shokai Co., Ltd., product name "PP (PP-N-BN)", thickness: 2 mm)

[0264] In addition, "G", "Cf" and "Zip" in the column of "Adhesion" in Table 1 have the following meanings, respectively.

[0265] G: Leaves a thin mark on the surface of the adherend.

[0266] Cf: Cohesive failure of the adhesive layer was observed.

[0267] Zip: A zipper phenomenon has occurred.

[0268] [Test Example 6] <Measurement of holding force>

[0269] The adhesive layer of the adhesive sheet (before UV) and the adhesive sheet (after UV) manufactured in the embodiment and the comparative example is attached to a stainless steel (SUS) plate (SUS304, 360 mesh polishing) as an adherend. At this time, the area where the adhesive layer is attached to the stainless steel plate is 25mm×25mm in size. After the stainless steel plate with the adhesive sheet thus attached is left to stand for 15 minutes under an environment of 23°C and 50%RH, it is set on a creep tester and further left to stand for 15 minutes in this state. Next, a load of 9.8N is applied to the adhesive sheet under an environment of 40°C, and the time (maximum 70,000 seconds) until the adhesive sheet falls off is measured according to the retention force determination method of JIS Z0237: 2009, which is used as the retention force (seconds) of the adhesive layer. The results are shown in Table 1.

[0270] In addition, "NC" and "Cf" in the "Retention Force" column of Table 1 have the following meanings, respectively.

[0271] NC: The adhesive sheet did not fall off even when the holding force was measured for more than 70,000 seconds, and the position of the adhesive sheet attached to the adherend did not shift.

[0272] Cf: Cohesive failure of the adhesive layer was observed.

[0273] [Test Example 7] <Calculation of CO2 introduction rate>

[0274] The CO2 introduction rate (mass %) in the aliphatic polycarbonate resin (polymer) prepared in the examples and comparative examples was calculated by the following calculation formula. The larger the value of the CO2 introduction rate, the more efficient the utilization of carbon dioxide. The results are shown in Table 1.

[0275] CO2 introduction rate [mass %] = (CO2 amount in polymer [g] / polymer amount [g]) × 100

[0276] CO2 content in polymer [g] = 44 × (carbonate ratio [%])

[0277] Polymer amount [g] = {(unit molecular weight of carbonate site in polymer) × (carbonate ratio [%])} + {(unit molecular weight of ether site in polymer) × (ether structural unit ratio [%])}

[0278] Carbonate ratio [%] = 100 - ether structural unit ratio [%]

[0279] [Table 1]

[0280]

[0281] According to Table 1, the aliphatic polycarbonate resin (before UV) of the embodiment uses carbon dioxide as a raw material for preparation, and has a low glass transition temperature (Tg), and can be used as an adhesive. In addition, the aliphatic polycarbonate resin crosslinked product (after UV) of the embodiment uses carbon dioxide as a raw material for preparation, and has a low glass transition temperature (Tg), which is suitable as an adhesive. In addition, the adhesive sheets (before UV) and adhesive sheets (after UV) of Examples 1 to 4, 7, 8 and 12 use carbon dioxide as a raw material for preparation, and both high-polarity materials and low-polarity materials have good adhesion, and the retention is also excellent.

[0282] Industrial Applicability

[0283] The aliphatic polycarbonate resin and the aliphatic polycarbonate resin crosslinked product of the present invention can be suitably used in adhesives, etc. Furthermore, the adhesive sheet of the present invention can be suitably used in both cases where a high-polarity material is used as an adherend and a low-polarity material is used as an adherend.

[0284] Description of Reference Numerals

[0285] 1A, 1B: adhesive sheets; 11: adhesive layer; 12, 12a, 12b: release sheets; 13: substrate.

Claims

1. An aliphatic polycarbonate resin having an ether structure in the main chain and having a structure formed by random copolymerization of a repeating unit represented by the following formula (Ia), a repeating unit represented by the following formula (Ib), a repeating unit represented by the following formula (Ic) and a repeating unit represented by the following formula (Id), [Chemical formula 1] In formula (Ia) and formula (Ib), R 1 and R 2 are hydrocarbon groups having 4 or more carbon atoms, and they may be the same or different from each other; in formula (Ic) and formula (Id), R 3 and R 4 are hydrocarbon groups having a crosslinkable functional group, and may be the same as or different from each other.

2. The aliphatic polycarbonate resin according to claim 1, characterized in that The crosslinkable functional group is a (meth)acryloyl group or an allyl group.

3. The aliphatic polycarbonate resin according to claim 1, characterized in that The R 3 or the R 4 Has an alkyl chain.

4. The aliphatic polycarbonate resin according to claim 1, characterized in that The R 3 or the R 4 It has an ether structure.

5. The aliphatic polycarbonate resin according to claim 1, characterized in that The R 3 or the R 4 Contains the structure represented by the following formula (II): CH2=CH-C(=O)-OXO- ···(II) In formula (II), X is an alkyl chain.

6. The aliphatic polycarbonate resin according to claim 1, characterized in that The aliphatic polycarbonate resin contains 0.01 mol % or more and 10 mol % or less of the crosslinkable functional group.

7. The aliphatic polycarbonate resin according to claim 1, characterized in that The aliphatic polycarbonate resin contains 0.1% by mass or more and 99% by mass or less of the unit of the ether structure on the main chain.

8. The aliphatic polycarbonate resin according to claim 1, characterized in that The aliphatic polycarbonate resin is a polymerization product of carbon dioxide and epoxide.

9. The aliphatic polycarbonate resin according to claim 1, characterized in that The aliphatic polycarbonate resin has a glass transition temperature (Tg) of 5° C. or less. 10 . An aliphatic polycarbonate resin crosslinked product, which is formed by crosslinking the aliphatic polycarbonate resin according to claim 1 .

11. The aliphatic polycarbonate resin cross-linked product according to claim 10, characterized in that: The aliphatic polycarbonate resin cross-linked product has a gel fraction of 15% to 85%.

12. The aliphatic polycarbonate resin cross-linked product according to claim 10, characterized in that: The aliphatic polycarbonate resin cross-linked product has a 5% weight loss temperature of 200° C. or higher and 450° C. or lower.

13. A method for preparing a cross-linked aliphatic polycarbonate resin, wherein: The aliphatic polycarbonate resin according to any one of claims 1 to 9 is irradiated with energy rays to crosslink the aliphatic polycarbonate resin.

14. An adhesive sheet comprising an adhesive layer composed of an adhesive, wherein the adhesive contains 50% by mass or more of an aliphatic polycarbonate resin having an ether structure in the main chain and a crosslinkable functional group in the side chain, The adhesive sheet has an adhesive force to polypropylene of 1.5 N / 25 mm or more.

15. An adhesive sheet comprising an adhesive layer composed of an adhesive, wherein the adhesive contains 50% by mass or more of an aliphatic polycarbonate resin crosslinked product, wherein the aliphatic polycarbonate resin crosslinked product is a crosslinked product of an aliphatic polycarbonate resin having an ether structure in the main chain and a crosslinkable functional group in the side chain, The adhesive sheet has an adhesive force to polypropylene of 1.5 N / 25 mm or more.

16. The adhesive sheet according to claim 15, characterized in that As the holding force in accordance with JIS Z0237: 2009, the adherend is stainless steel, the attachment area is 25 mm×25 mm, the temperature during the test is 40° C., and a load of 9.8 N is applied, and the time until the adhesive sheet falls off is 8000 seconds or more.

17. The adhesive sheet according to claim 14, characterized in that The aliphatic polycarbonate resin is the aliphatic polycarbonate resin according to any one of claims 1 to 9.

18. The adhesive sheet according to claim 15, characterized in that The aliphatic polycarbonate resin cross-linked product is the aliphatic polycarbonate resin cross-linked product according to claim 10.

Citation Information

Patent Citations

  • Photopolymerizable composition, pressure-sensitive adhesive, and pressure-sensitive adhesive sheet

    JP2003096116A

  • Polyalkylene carbonate resin and method for producing the same

    JP2015533920A